Comics and science fiction in West Bengal - Cappello, Daniela (Interdisziplinäre Zeitschrift für Südasienforschung, 2019)
In this paper I look at four examples of Bengali SF (science fiction) comics by two great authors and illustrators of sequential art: Mayukh Chaudhuri (Yātrī, Smārak) and Narayan Debnath (Ḍrāgoner thābā, Ajānā deśe). Departing from a con-ventional understanding of SF as a fixed genre, I aim at showing that the SF comic is a ‘mode’ rather than a ‘genre’, building on a very fluid notion of boundaries between narrative styles, themes, and tropes formally associated with fixed genres. In these Bengali comics, it is especially the visual space of the comic that allows for blending and ‘contamination’ with other typical features drawn from adventure and detective fiction. Moreover, a dominant thematic thread that cross-cuts the narratives here examined are the tropes of the ‘other’ and the ‘unknown’, which are in fact central images of both adventure and SF: the exploration and encounter with ‘unknown’ (ajānā) worlds and ‘strange’ species (adbhut jāti) is mirrored in the usage of a lan-guage that expresses ‘otherness’ and strangeness. These examples show that the medium of the comic framing the SF story adds further possibilities of reading ‘genre hybridity’ as constitutive of the genre of SF as such.